Huperzia saururus increases memory retention in rats - Vallejo, Mariana Guadalupe (2007)
Huperzia saururus is reported in Argentinean popular medicine as a memory improver. Chemical studies have shown that the main constituents of the species are Lycopodium alkaloids. On the basis of this information, a purified alkaloid extract was obtained by alkaline extraction of the aerial parts. The aim of this work was to investigate the effects of intra-hippocampal administration of the purified alkaloid extract (AE) on memory retention in vivo, using a step down test, in order to correlate with previous results obtained in vitro in an electrophysiological model. The AE administration significantly increased the latency time in comparison to control animals. For treated animals the latency time was 37.61 ± 2.84, 80.94 ± 2.37, and 180.00 ± 5.74 s for 1, 5, and 10 ng/rat, respectively versus 14.89 ± 2.38 s for controls. According to these results there is a good relationship between the ethnopharmacological use and the effects hereby showed.